Presupposition as a Persuasive Strategy in the Ordinary’s Instagram Advertisment - Silva Saputri; Udayani Permanaludin; Toneng Listiani (Journal of English Language and Education, 2026)
Presupposition is an important pragmatic strategy in advertising because it enables advertisers to communicate persuasive meanings implicitly. Although previous studies have examined presupposition in advertising discourse, limited attention has been given to its persuasive functions in Instagram-based skincare advertising, particularly in The Ordinary’s advertisements. Therefore, this research aims to analyze the types of presupposition and their persuasive functions in The Ordinary’s Instagram advertisement captions. A qualitative descriptive method was employed using captions posted on The Ordinary’s official Instagram account between November 2025 until January 2026. Data were collected through observation and documentation techniques and analyzed using Yule’s (1996) theory of presupposition. The findings revealed 31 instances of presupposition, consisting of lexical, existential, factive, and structural types, with lexical presupposition occurring most frequently. Presuppositions functioned to normalize skincare practices, strengthen product relevance, enhance brand credibility, and encourage audience engagement. These findings demonstrate the importance of presupposition as a persuasive strategy in digital advertising discourse.